The Parish Clergy's Ministry of Prayer with Hospitalized Parishioners - VandeCreek, Larry (Journal of psychology and theology, 1998)
Previous reports suggest that clergy frequently pray with parishioners during hospital visits. In this study, 286 parish clergy and lay volunteers characterize these prayers as meditative, liturgical, or extemporaneous. Content for the latter two categories is further described as intercession, confession, or thanksgiving/praise. Respondents reported 44,403 hospital pastoral visits during the previous year and most, regardless of faith group, estimated that they prayed during 100% of these visits. Further, these prayers were usually extemporaneous intercession; meditative and liturgical prayers were used less frequently. Despite the demonstrated association between prayer and mystical experiences, clergy mysticism scores were significantly lower than those reported in the literature and were not significantly related to the style or content of prayers during hospital visits.